Development of Learning Tools Based on Realistic Mathematics Education to Improve the Mathematical Problem-Solving Ability of Students in Class VII Middle School - Putri, Febby Fauzila; Yerizon, Yerizon; Arnawa, I Made (Journal of Social Research, 2023)
This research aims to describe: 1) the effectiveness of the realistic approach-based learning tools developed; 2) increasing students' mathematical problem-solving skills taught through a developed realistic approach-based learning tool; and 3) student responses to the realistic approach-based learning tools developed. This research is a development research. This research was conducted in two stages, namely the first stage of developing learning tools based on the Realistic Mathematics Education approach, and the second stage of testing learning tools based on the Realistic Mathematics Education approach developed in class VII at SMP IT Darul Ikhlas Al Islami to see their effectiveness. The results of the trial, it was obtained: 1) learning tools based on a realistic approach that were developed effectively, in terms of a) classical student learning completeness; b) achievement of learning objectives; and c) learning time; 2) The realistic approach-based learning tools developed can improve students' mathematical problem-solving abilities; and 3) students' positive response to the activities and learning tools based on the realistic approach developed.